A Study to Determine the Impact of a Structure Teaching Program on the Knowledge of Needle Stick Injury Among Hospital Staff Nurses - Mahendra Kumawat; Priyesh M. Bhanwara Jain (International Journal of Community Health Nursing And Practices, 2023)
Needle stick injuries occur when needles accidentally puncture the skin, posing a risk to individuals working with hypodermic syringes and other needle equipment, particularly in healthcare settings. These injuries are recognized as occupational hazards in the medical field and raise concerns about the potential transmission of blood-borne illnesses, including hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV). Although the immediate physical effects of needle stick injuries are typically minor, they can result in the spread of infectious diseases, increasing the risk of infection for those exposed. Needle sticks have been identified as a workplace hazard. Nursing attendants working around patients or normal models stand risk of incidental receptiveness to blood and blood borne microorganisms. Such disasters are connected with nearly nothing, yet basic risk to clinical consideration capable calling, prosperity, families and moreover patients. It has been evaluated that more than 1 million needle stick wounds are represented each year and each needle stick might potentially be overpowering. Tertiary thought association is the place where patient weight is consistently high and clinical benefits workers have high liability and are largely more generally connected with strategies which can incite NSI. These establishments ought to have office and clear procedure concerning real evacuation of sharps, NSI observation and Post receptiveness prophylaxis for confirmation of adequacy of their Medical caretakers.
Keywords: Needle stick injuries; hepatitis B virus; hepatitis C virus; human immunodeficiency virus; infectious diseases